2003
DOI: 10.1016/s1044-0305(03)00201-0
|View full text |Cite
|
Sign up to set email alerts
|

Detection and characterization of methionine oxidation in peptides by collision-induced dissociation and electron capture dissociation

Abstract: Electron capture dissociation (ECD) and collision-induced dissociation (CID), the two complementary fragmentation techniques, are demonstrated to be effective in the detection and localization of the methionine sulfoxide [Met(O)] residues in peptides using Fourier transform ion cyclotron resonance (FTICR) mass spectrometry. The presence of Met(O) can be easily recognized in the low-energy CID spectrum showing the characteristic loss of methanesulfenic acid (CH 3 SOH, 64 Da) from the side chain of Met(O). The p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
0
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(97 citation statements)
references
References 52 publications
2
93
0
2
Order By: Relevance
“…One promising solution to this problem is the development of "softer" fragmentation techniques such as electron transfer dissociation (ETD) and electron capture dissociation (ECD). For example, Guan et al [129] showed that CID of oxidised methionine containing peptides resulted in the loss of CH 3 SOH whereas ECD allowed fragmentation of the peptide backbone while preserving the side-chain oxidation, thus allowing direct location of the oxidised methionine.…”
Section: Mass Spectrometric and Bioinformatics Challengesmentioning
confidence: 99%
“…One promising solution to this problem is the development of "softer" fragmentation techniques such as electron transfer dissociation (ETD) and electron capture dissociation (ECD). For example, Guan et al [129] showed that CID of oxidised methionine containing peptides resulted in the loss of CH 3 SOH whereas ECD allowed fragmentation of the peptide backbone while preserving the side-chain oxidation, thus allowing direct location of the oxidised methionine.…”
Section: Mass Spectrometric and Bioinformatics Challengesmentioning
confidence: 99%
“…Methionine is one of the most readily oxidized amino acid constituents of proteins [5,[11][12][13]. Oxidation of methionine residues can result in significant conformational and/or functional changes [14], and thus represents an important posttranslational modification under conditions of oxidative stress or aging [15].…”
Section: Introductionmentioning
confidence: 99%
“…These hydrogen bonds would provide extra stabilization for [Mϩ2H] -4]. ECD also plays a useful role in characterization and localization of post-translational modifications (PTMs) as it preserves labile PTMs in protein [5][6][7] while cleaving the protein backbone to give series of specific fragment ions. This is in contrast with that of conventional slow-heating ion dissociation methods [8,9], such as collision induced dissociation (CID) [10 -12] and infrared multiproton dissociation (IRMPD) [13].…”
mentioning
confidence: 99%
“…(J Am Soc Mass Spectrom 2010, 21, 1235-1244) © 2010 Published by Elsevier Inc. on behalf of American Society for Mass Spectrometry E lectron capture dissociation (ECD) is an important tandem mass spectrometry (MS/MS) tool for sequencing multiply-charged peptides/proteins [1][2][3][4]. ECD also plays a useful role in characterization and localization of post-translational modifications (PTMs) as it preserves labile PTMs in protein [5][6][7] while cleaving the protein backbone to give series of specific fragment ions. This is in contrast with that of conventional slow-heating ion dissociation methods [8,9], such as collision induced dissociation (CID) [10 -12] and infrared multiproton dissociation (IRMPD) [13].…”
mentioning
confidence: 99%